2011
DOI: 10.1177/1527002511404783
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Demand for Televised Live Football: Features of the German National Football Team

Abstract: This study analyzes all 216 broadcasts of the German national football team from January 1993 to June 2008 to identify which factors ensure the success of televised sport broadcasts. The results reveal that demand depends mostly on the type of match and its importance in a tournament context. Viewers prefer a national team with established star players and high-quality opponents. Factors unrelated to the sport, such as the kickoff time or weather, have some influence, but coaches and holidays are insignificant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 19 publications
8
69
0
Order By: Relevance
“…In similar studies, Feddersen and Rott (2011), concluded that star players and the opposition quality were of greater importance than non-match variables such as the start time and weather conditions. Earlier work by Hammervold and Solberg (2006), found there was a clubs would lose the fewest gate receipts ticket, therefore generating the largest gain from the broadcast rights paid by the subscription provider BSkyB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In similar studies, Feddersen and Rott (2011), concluded that star players and the opposition quality were of greater importance than non-match variables such as the start time and weather conditions. Earlier work by Hammervold and Solberg (2006), found there was a clubs would lose the fewest gate receipts ticket, therefore generating the largest gain from the broadcast rights paid by the subscription provider BSkyB.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Szymanski (2001) first contrasted the utility of committed local fans and neutral TV viewers, while Forrest, Simmons, and Buraimo (2005) were the first to test this notion empirically. At the same time, recent studies by Tainsky and McEvoy (2012) and Feddersen and Rott (2011) show that uncertainty of outcome and team quality are important determinants of TV viewership. Naturally, this enumeration is far from exhaustive.…”
Section: Related Literaturementioning
confidence: 99%
“…However, the influence of this characteristic was limited as the TV audience was predicted to increase by only 6.3 per cent when the match uncertainty variable was 'improved' by one stan- Table 5 in Cave and Crandall (2001) also provides some calculations on broadcast revenue dard deviationrepresenting a game of almost complete equality. Feddersen and Rott (2012), in a study on viewer demand for TV broadcasts of the German national football team, found that demand depends mostly on the context of the match in the tournament and that high-quality opponents are preferred. A recent National Football League (NFL) study by Paul and Weinbach (2007) revealed evidence of strong preferences for unpredictable and highscoring contests.…”
Section: Literature Reviewmentioning
confidence: 99%